2007
DOI: 10.1016/j.ces.2006.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Production of hydrogen and sulfur from hydrogen sulfide in a nonthermal-plasma pulsed corona discharge reactor

Abstract: Hydrogen sulfide (H 2 S) dissociation into hydrogen and sulfur has been studied in a pulsed corona discharge reactor (PCDR). Due to the high dielectric strength of pure H 2 S (~2.9 times higher than air), a non-thermal plasma could not be sustained in pure H 2 S at discharge voltages up to 30 kV with our reactor geometry. Therefore, H 2 S was diluted with another gas with lower dielectric strength to reduce the breakdown voltage. Breakdown voltages of H 2 S in four balance gases (Ar, He, N 2 and H 2) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…Yellow sulfur was observed at the waste gas output, which is consistent with previous H 2 S dissociation experiments in a pulsed corona discharge reactor [24]. SO 2 is a common gaseous pollutant and can appear along with H 2 S. Its emission spectrum was also investigated in this experiment.…”
Section: Cold Excitation Of H 2 S In the Dbd Microplasmasupporting
confidence: 86%
“…Yellow sulfur was observed at the waste gas output, which is consistent with previous H 2 S dissociation experiments in a pulsed corona discharge reactor [24]. SO 2 is a common gaseous pollutant and can appear along with H 2 S. Its emission spectrum was also investigated in this experiment.…”
Section: Cold Excitation Of H 2 S In the Dbd Microplasmasupporting
confidence: 86%
“…This layer of sulfur, which is not chemically bonded to carbon of the polymer substrate, may be in the form of polysulfides -S x - because sulfur tends to catenate (bind to itself by the formation of chains), but the formation of any type of polysulfide is almost impossible to confirm by our experimental techniques. The appearance of unbonded sulfur has been described in several reports, in which plasma-assisted decomposition of H 2 S was investigated to develop a method for destroying this environmentally problematic gas, which is produced in the oil refinement industry [13,17,18,19,20]. These studies found direct decomposition into H 2 and S, which was deposited on the reactor wall [19].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the conventional treatment method for H 2 S destruction is the Claus process, which produces sulfur, whereas hydrogen is converted to water and therefore lost [12,18]. This is the reason why plasma has been investigated as a promising alternative technique for H 2 S decomposition into hydrogen and sulfur and thus for hydrogen production, which is of strong commercial interest [19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…These observations can be explained by analysis of electron collision processes for monatomic and diatomic gases. 2 When an energetic electron collides with an monatomic molecule like Ar, the electron predominantly experiences elastic collision without energy loss, if the electron energy is less than the excitation energy of target atom. The electron is then further accelerated in the electric field and hence gains more energy.…”
Section: Resultsmentioning
confidence: 99%